Variation in Stored Nutrients in Culms of Dendrocalamus strictus and their Effect on Rooting of Culm Cuttings as Influenced by the Method of Planting - Gupta, B. N.; Pattanath, P. G. (Indian Forester, 1976)
This paper presents a study on correlation or seasonal variatlon in stored nutrients in culms of Dendrocalamus strictus Nees and the performance of culm cuttings as propagules. Statistical analysis of the data collected on seasonal variation in nitrogen, phosphorus, potassium, calcium, magnesium and moisture content revealed that seasonal variation was significant for all elements except potassium. Besides this, nitrogen and phosphorus were found to exhibit a positive and significant correlation with vigour. The performance of the propagules also varied significantly with different months of planting. April was found to be the best month for the preparation of cuttings. The method of planting also was observed to have a significant influence on the performance of the propagules. Statistical analysis showed that vertical and oblique methods or planting which rail under the same bar is significantly different from the horizontal method at 0.1% level of probability.